Thermal Activation of Phosphate Raw Materials in the Presence of Alkaline Salts - Akhtamova Maftuna Zaynitdin qizi (Research Parks Publishing LLC, 2021)
The thermal-alkaline method of phosphate processing makes it possible to involve in industrial production not only ordinary phosphorite flour, but also production wastes, with the subsequent production of high-quality fertilizers with a high content of digestible forms of phosphorus, potassium, calcium, magnesium and other components. Thus, both the problems of rational use of mineral raw materials and many environmental problems, the creation of new technologies for processing waste from mining and chemical industries and reserves of refractory phosphates are solved. An important indicator of the produced fertilizers is their cost. It should be born in mind that one should not strive for a 100% production of mineral fertilizers in concentrated and complex forms, which are relatively expensive, since this would contradict questions about the economic efficiency of the use of mineral resources. In this respect, a relatively cheap method based on the thermal alkaline activation of phosphate raw materials deserves some attention. The main part of phosphorus and calcium in thermo-alkaline fertilizers is in a lemon-soluble form, that is, the latter has a prolonged effect. According to leading agrochemists, agriculture can get a significant effect from the use of long-acting fertilizers, which are practically not washed out and are not lost in the soil. In such fertilizers, phosphorus can be used by plants for several years. In this regard, the development of acid-free methods for processing phosphate raw materials, including raw materials poor in phosphorus content, is currently relevant.